Competition, Diversification, and Stability: A Study at an Islamic Bank in Indonesia - Rachma Revida, Djuminah,; Septiarini, Dina Fitrisia (Opción, 2019)
This research reviews the level of competition between banks, diversification of income sources, and banking stability in Indonesia. The level of competition is measured by the Panzar-Rosse method, diversification of income sources is measured by loan focus and income focus index, and banking stability is measured by (ZScore= ZROA). Result analysis finds that the Islamic banking competition in Indonesia is monopolistic, while the diversification of lending in Islamic banks is well diversified. In conclusion, the stability condition of Islamic banking in Indonesia, especially Islamic commercial banks are very steady and tends to increase the level of stability.